Agents and Artificial Intelligence 6th International Conference, ICAART 2014, Angers, France, March 6-8, 2014, Revised Selected Papers - Duval, Béatrice; van den Herik, Jaap; Loiseau, Stephane; Filipe, Joaquim (Lecture Notes in Artificial Intelligence,, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Conference on Agents and Artificial Intelligence, ICAART 2014, held in Angers, France, in March 2014. The 21 revised full papers presented together with one invited paper were carefully reviewed and selected from 225 submissions. The papers are organized in two topical sections on agents and on artificial intelligence.